Comparison of communication and personal characteristics of living kidney donors and a matched quota sample. (16th October 2012) - Smith, Sandi W.; Hitt, Rose; Nazione, Samantha; Lauckner, Carolyn; Park, Hee Sun; Sung, Randall; Leichtman, Alan
Abstract Deceased organ donation does not meet the need for kidney transplants. Thus, it is important to examine topics relevant to kidney donors such as communication leading to the donation decision and donor characteristics. This study reports personal characteristics and communication leading to the decision to donate among living kidney donors and a demographically matched quota sample. Donors had higher scores for compassion, while non‐donors reported more volunteerism. Donors and non‐donors did not differ in conversation or conformity orientations of family communication styles. Only 4.7% of donors reported being asked to donate directly. Matched respondents reported feeling more comfortable than unsettled with the idea of being asked directly and indicated a preference to learn of the need directly or indirectly, giving them the option to volunteer. The majority of donors were giving to family members and friends, and the matched sample indicated greater willingness to donate to immediate family members, followed by friends. Practical implications of the findings are offered.